IIMPLEMENTING COMMUNICATIVE LANGUAGE TEACHING (CTL) APPROACH IN AN INTERNATIONAL STANDARD SCHOOL IN BATAM - Gea Carnando; Nurlaily Nurlaily (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2020)
Various teaching approaches have been developed all the time tomeet the learners' needs and to achieve the objective of learning successfully.One of the most popular and effective approaches that has been developed isCommunicative Language Teaching (CLT). Many scholars have foundimplementing CLT is challenging since it needs certain criteria of learners toengage with the whole process. This research investigated whether the CLTapproach fits perfectly in one of the International schools in Batam. ClassAction Research with 2 cycles was employed with 19 twelfth grade studentsparticipated in the study. Data were collected by having observation: checklistand notetaking. The result showed that CLT was a suitable method for thestudents. It was evaluated by the classroom engagement that improvedgradually. Cycle I and II result were compared using the motivationalconceptualization of engagement instruments. It was also found out that CLT ischallenging ways that influence the learners' behaviour to finally gainknowledge.